Epigenetic Transgenerational Modifications Induced by Xenobiotic Exposure in Zebrafish - Terrazas-Salgado, Luis; García-Gasca, Alejandra; Betancourt-Lozano, Miguel; Llera-Herrera, Raúl; Alvarado-Cruz, Isabel; Yáñez-Rivera, Beatriz (Frontiers in Cell and Developmental Biology, 2022)
Zebrafish (Danio rerio) is a well-established vertebrate model in ecotoxicology research that responds to a wide range of xenobiotics such as pesticides, drugs, and endocrine-disrupting compounds. The epigenome can interact with the environment and transform internal and/or external signals into phenotypic responses through changes in gene transcription. Environmental exposures can also generate epigenetic variations in offspring even by indirect exposure. In this review, we address the advantages of using zebrafish as an experimental animal model to study transgenerational epigenetic processes upon exposure to xenobiotics. We focused mostly on DNA methylation, although studies on post-translational modifications of histones, and non-coding RNAs related to xenobiotic exposure in zebrafish are also discussed. A revision of the methods used to study epigenetic changes in zebrafish revealed the relevance and reproducibility for epigenetics-related research. PubMed and Google Scholar databases were consulted for original research articles published from 2013 to date, by using six keywords: zebrafish, epigenetics, exposure, parental, transgenerational, and F2. From 499 articles identified, 92 were considered, of which 14 were selected as included F2 and epigenetic mechanisms. Current knowledge regarding the effect of xenobiotics on DNA methylation, histone modifications, and changes in non-coding RNAs expressed in F2 is summarized, along with key experimental design considerations to characterize transgenerational effects.